2022
DOI: 10.3389/fcimb.2022.977591
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic next-generation sequencing indicates more precise pathogens in patients with pulmonary infection: A retrospective study

Abstract: BackgroundTimely identification of causative pathogens is important for the diagnosis and treatment of pulmonary infections. Metagenomic next-generation sequencing (mNGS), a novel approach to pathogen detection, can directly sequence nucleic acids of specimens, providing a wide range of microbial profile. The purpose of this study was to evaluate the diagnostic performance of mNGS in the bronchoalveolar lavage fluid (BALF) of patients with suspected pulmonary infection.MethodsFrom April 2019 to September 2021,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…As the reported incidence of pulmonary tuberculosis has been declining consistently for more than 10 years, China is still one of the high tuberculosis burden countries, accounting for 7.1% of all estimated incident cases worldwide [9]. In this study, Mycobacterium tuberculosis complex was the most common identi ed pathogen, with a detection rate of 16.5%, similar to several previous studies using mNGS analysis [10][11]. The sensitivity of mNGS for tuberculosis diagnosis has been proven to be similar to Xpert MTB/RIF assay and culture [12].…”
Section: Discussionsupporting
confidence: 85%
“…As the reported incidence of pulmonary tuberculosis has been declining consistently for more than 10 years, China is still one of the high tuberculosis burden countries, accounting for 7.1% of all estimated incident cases worldwide [9]. In this study, Mycobacterium tuberculosis complex was the most common identi ed pathogen, with a detection rate of 16.5%, similar to several previous studies using mNGS analysis [10][11]. The sensitivity of mNGS for tuberculosis diagnosis has been proven to be similar to Xpert MTB/RIF assay and culture [12].…”
Section: Discussionsupporting
confidence: 85%
“…So, we successfully diagnosed cutaneous anthrax through mNGS on FFPE tissues, promptly treated the patient with penicillin and achieved a good prognosis. The application of mNGS technology in medicine also has certain limitations, such as complex operations, high costs, and the detection process has not yet been standardized, and in the absence of a unified standard for the mNGS biochemical analysis process, users choose biochemical analysis software based on personal experience and simplicity, which will affect the repeatability of experiments and the reliability of results ( Han et al., 2019 ; Wu et al., 2022 ). However, there is potential for cost reductions due to increased demand and technological development.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-free DNA sequencing and other state-of-the-art molecular methods are showing their usefulness in the etiological diagnosis of IE, especially in those with negative bacterial cultures [ 92 , 93 ]. A representative example is metagenomic next-generation sequencing, which according to clinical studies published to date has a higher sensitivity than classical diagnostic methods [ 94 , 95 ]. Duan et al [ 96 ] analyzed a group of 109 patients, both with and without different infectious pathologies, and demonstrated that although the sensitivity of the method is superior, no statistically significant differences were reported in specificity compared to cultures ( p = 0.41).…”
Section: From Pathophysiology To Multidisciplinary Assessmentmentioning
confidence: 99%